Estudo epidemiológico da raiva, caracterização antigênica de cepas do vírus da raiva isoladas na Amazônia brasileira - CASSEB, Livia Medeiros Neves (Universidade Federal do Pará, 2013)
Aiming to evaluate the epidemiology of rabies, new diagnostic procedures – antigenic and genetic characterization - were included in this study to investigate the epidemiologic profile of animal rabies in the Brazilian Amazon region, between January 2000 and July 2009. A careful revision of information of Central Nervous System (CNS) samples received and examined at Rabies Laboratory of Instituto Evandro Chagas was performed. A total of 265 rabies virus strains isolated from CNS samples of humans (33) and domestic/sylvatic animals (232) were antigenically characterized by indirect immunofluorescent assay (IFA) using a panel of eight monoclonal antibodies against the rabies virus nucleoprotein produces by the CDC; moreover, from 21 of them the nucleoprotein (gene N) was partially characterized by nucleotide sequencing followed by phylogenetic analyzes. Obtained sequences were compared internally and with other rabies virus sequences from Brazil and other American countries, using the Bayesian and maximum likelihood methods. It was observed a lower transmission of rabies virus in urban areas; the detection of the rural cycle of rabies in almost all Amazonian states; the occurrence of aerial rabies cycle in Pará and Amapá states; identification of rabies virus variant 2 (AgV2) among domestic dogs and cats as the main viral transmission mechanism; detection of circulating antigenic variants AgV3, AgV4 and “Eptesicus” variant in sylvan animals; and finally, reduction of dog-to-man transmission of rabies virus which was replaced by an increasing of bat-to-man transmission cycle, especially in Pará state. In conclusion, the association of antigenic and molecular techniques resulted in a better understanding of rabies molecular epidemiology in the Amazon region.